Does dependency make a difference? The role of convenience, social influence, facilitating condition and self-efficacy on student's purchase behaviour of smartphone - Jaganathan, Mathivannan; Mustapa, Azrain Nasyrah; Wan Hasan, Wan Azlina; Nik Mat, Nik Kamariah; Alekam, Jamal Mohammed Esmail (2014)
It is an undeniable fact that penetration level and usage and sales of Smartphone dramatically increased past few years, whereby; it has increased to almost 60 percent of total population.Despite the high penetration of smartphone, previous studies have exhibited inconsistent findings towards understanding the behavioral intention to use smartphone especially among university students. Thus, the purpose of this study is to examine purchasing behavior of Smartphone among students. From the literature, five antecedents of purchasing behavior were identified.Each variable is measured using 7-point Like rt scale: convenience (10 items), social influence (6 items), self-efficacy (10 items), facilitating condition (11 items), dependency (14 items) and purchasing behavior (4 items). Using the primary data collection method, 400 questionnaires were distributed to the target respondents of one of the public higher education in the northern region.The responses collected were 350 completed questionnaires representing 87.5 percent response rate.The data were analysed using Structural Equation Modeling (SEM) using AMOS. Confirmatory factor analysis of measurement models indicates adequate goodness or fit after few items were eliminated through modification indices verification.Therefore, goodness of fit for the generated structural model shows the adequate fit.This study has established four direct significant causal effects and two significant mediating effects: (1) convenience and dependency, (2) social influence and dependency, (3) facilitating condition and purchase behavior, (4), dependency and purchase behavior.The significant mediating results are: (1).Dependency mediates the relationship between convenience and purchase behavior; (2) dependency mediates social influence and purchase behavior.Thus, findings suggested that convenience, social influence and dependency play a role in determining students purchase behavior of smartphone.The researchers hope the findings of this study will contribute theoretically and practically to scholars, marketers and smartphone manufacturers.